Trend Analysis: Consumer Behavior towards the Decision to Use Shopee Paylater - Serenade, Vincensia; Gusniar, Bella; Rahmasari, Yunita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2024)
Financial Technology (Fintech) has significantly transformed the financial landscape by integrating traditional financial systems with modern technology. This study examines consumer behavior towards Shopee PayLater, a prominent